Advanced C and C++ Compiling - Stevanovic, Milan (Apress : Imprint: Apress, 2014)
Learning how to write C/C++ code is only the first step. To be a serious programmer, you need to understand the structure and purpose of the binary files produced by the compiler: object files, static libraries, shared libraries, and, of course, executables. Advanced C and C++ Compiling explains the build process in detail and shows how to integrate code from other developers in the form of deployed libraries as well as how to resolve issues and potential mismatches between your own and external code trees. With the proliferation of open source, understanding these issues is increasingly the responsibility of the individual programmer. Advanced C and C++ Compiling brings all of the information needed to move from intermediate to expert programmer together in one place -- an engineering guide on the topic of C/C++ binaries to help you get the most accurate and pertinent information in the quickest possible time.